2014
DOI: 10.1016/j.cbpb.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Persistent impaired glucose metabolism in a zebrafish hyperglycemia model

Abstract: Diabetes mellitus (DM) affects over 10% of the world's population. Hyperglycemia is the main feature for the diagnosis of this disease. The zebrafish (Danio rerio) is an established model organism for the study of various metabolic diseases. In this paper, hyperglycemic zebrafish, when immersed in a 111 mM glucose solution for 14 days, developed increased glycation of proteins from the eyes, decreased mRNA levels of insulin receptors in the muscle, and a reversion of high blood glucose level after treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 39 publications
3
97
0
6
Order By: Relevance
“…After, we performed the evaluation of the E-NTPDases, ada-related, and adora gene expressions from encephala of adult zebrafish. The blood glucose levels from glucose-treated and washout animals demonstrated the same profile already developed in previous works [8,42]. Nucleotides are important extracellular messengers in both physiological and pathological conditions [11].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…After, we performed the evaluation of the E-NTPDases, ada-related, and adora gene expressions from encephala of adult zebrafish. The blood glucose levels from glucose-treated and washout animals demonstrated the same profile already developed in previous works [8,42]. Nucleotides are important extracellular messengers in both physiological and pathological conditions [11].…”
Section: Discussionsupporting
confidence: 76%
“…Our results demonstrated that ecto-ADA activity was significantly increased in 111-mM glucose group, suggesting a decrease in adenosine levels in synaptic cleft. There is some consensus that a decrease of adenosine levels could be related with cognitive impairment observed in diabetic rats [8,55,56], which also could be suggested occurring in the zebrafish hyperglycemic model.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations